Functional Coatings From Formulation in Solution to Applications on Surfaces and Interfaces (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book brings together featured papers that relate to several technologically important applications of coatings. These range from non-wetting coatings to underwater resistance and biomedical implant surfaces. In particular, nine interesting coating works have been collected with specific applications in the plasma treatment of polymers for superhydrophobicity, special coatings for glass glazing modification, non-sticky special inorganic coatings for polymeric surfaces, surfactant-controlled cationic polymer self-assembly from solutions, silicone-modified waterborne acrylic emulsion coatings, coating deamination/degradation resistance to corrosive water immersion, surface texturing of concrete to improve coating adhesion, electrochemical polymeric coatings for surgical implants and outdoor fungal growth mechanisms on various polymeric coatings. In terms of coating materials, the researchers have studied polystyrene, acrylic emulsions, epoxy formulations, vinylic polymers, alkyd coats, biopolymers, inorganic alloys such as CrN; CrAlN; CrAlSiN, and cationic polymers. Although the papers are diverse, there are several common attributes that each paper addresses in one way or another. For instance, adhesion failure under certain environmental conditions, hydrophobicity or non-stick performance, effect of substrate texture and resistance to biofouling. The collection will serve as a valuable reference for anyone wishing to stay abreast of the latest advances in the realm of specialized technological coatings.